1984
DOI: 10.1007/bf01655131
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of organ‐cultured fetal pancreas: Experimental studies and potential clinical application in diabetes mellitus

Abstract: Transplantation of organ-cultured fetal islets of Langerhans may be one way of overcoming the dual difficulties of finding a suitable source of tissue and controlling graft rejection. Experiments in mice have clearly shown that fetal pancreas is an excellent source of islets. Tissue from one donor can be used to treat one or more recipients and provides excellent control of drug-induced diabetes, including prevention of diabetic renal microangiopathy. The fetal islets display selective survival in vitro and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 44 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…We generally placed the grafts under the renal capsule where islets derived from less than one half of a foetal pancreas produced euglycaemia in each recipient (Mandel, 1984). However, these grafts drained insulin into the systemic venous circulation and therefore the physiological first-pass of the hormone through the liver was absent (Madison et al, 1958;Blackard and Nelson, 1971;Felig, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We generally placed the grafts under the renal capsule where islets derived from less than one half of a foetal pancreas produced euglycaemia in each recipient (Mandel, 1984). However, these grafts drained insulin into the systemic venous circulation and therefore the physiological first-pass of the hormone through the liver was absent (Madison et al, 1958;Blackard and Nelson, 1971;Felig, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from this laboratory have clearly shown that it is possible to reverse streptozotocin-induced diabetes in mice with either isografts (Mandel, 1984) or allografts (Collier and Mandel, 1983;Georgiou and Mandel, 1984;Georgiou and Mandel, 1985a and b) of organ-cultured foetal pancreas. We generally placed the grafts under the renal capsule where islets derived from less than one half of a foetal pancreas produced euglycaemia in each recipient (Mandel, 1984). However, these grafts drained insulin into the systemic venous circulation and therefore the physiological first-pass of the hormone through the liver was absent (Madison et al, 1958;Blackard and Nelson, 1971;Felig, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies of both islet allotransplantation and xeno‐transplantation after streptozotocin treatment have shown rapid rejection of these grafts [3,5,27,36,37,43,44]. Thus, it is unlikely that streptozotocin prevented the onset of autoimmunity and reversed it in our studies simply on the basis of its mild immunosuppressive properties.…”
Section: Discussionmentioning
confidence: 83%